"I Would Do HIV Adoption 100 Times Over Again": An Exploratory Study on Families With Internationally Adopted Children With PHIV. Issue 1 (2nd January 2016) - Gibson, Eliza; Fair, Cynthia D.
ABSTRACT: Internationally adopted children with perinatally acquired HIV (PHIV) are an emerging population in the United States. One key informant and nine mothers of internationally adopted children with PHIV were interviewed about the adoption process, HIV disclosure, and family needs. Qualitative analyses of transcribed interviews revealed that faith played a pivotal role in pursuing "HIV adoption." Many participants expressed initial fear about adopting a child with PHIV, but gained confidence through education on transmission risks and the improved lifespan of children with PHIV. Participants reported few HIV-related challenges. Many actively promoted the international adoption of children with PHIV and used disclosure as a tool for education.